2014
DOI: 10.1186/1756-3305-7-151
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of alternative splicing in parasitic nematode transcriptomes

Abstract: BackgroundAlternative splicing (AS) of mRNA is a vital mechanism for enhancing genomic complexity in eukaryotes. Spliced isoforms of the same gene can have diverse molecular and biological functions and are often differentially expressed across various tissues, times, and conditions. Thus, AS has important implications in the study of parasitic nematodes with complex life cycles. Transcriptomic datasets are available from many species, but data must be revisited with splice-aware assembly protocols to facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
2
3
0
Order By: Relevance
“…This ratio is very close to the proportions recorded for Dictyocaulus viviparus (34.6%) (Cantacessi et al, 2010) and Cooperia oncophora (33.1%) (Heizer et al, 2013), but is significantly higher than that reported for C. elegans (17%) in WormBase (Yook et al, 2012). This result is consistent with observations of parasitic nematode transcriptomes (Abubucker et al, 2014), which may be due to a reduction in the number of functional genes in parasite genomes (Zheng H. et al, 2013) or the increased genomic complexity that may be required to interact with multiple hosts/vectors (Abubucker et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…This ratio is very close to the proportions recorded for Dictyocaulus viviparus (34.6%) (Cantacessi et al, 2010) and Cooperia oncophora (33.1%) (Heizer et al, 2013), but is significantly higher than that reported for C. elegans (17%) in WormBase (Yook et al, 2012). This result is consistent with observations of parasitic nematode transcriptomes (Abubucker et al, 2014), which may be due to a reduction in the number of functional genes in parasite genomes (Zheng H. et al, 2013) or the increased genomic complexity that may be required to interact with multiple hosts/vectors (Abubucker et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…By merging genomics and transcriptomics data, we can provide important insights into the molecular mechanisms regulated through alternative splicing. Alternative splicing is highly prevalent within H. glycines, echoing similar observations in other nematode species [48].…”
Section: Discussionsupporting
confidence: 72%
“…In addition, unique transcripts in symbiotic nematodes might also result from alternative splicing (AS) under specific physiological condition (here presence of bacterial symbionts). Nematodes are known to have AS in the range of 20–30%, typically with 2–3 transcripts per AS locus [ 31 ]. However, a deeper analysis of the AS in our experimental conditions is beyond the scope of this study and will be taken up in future.…”
Section: Discussionmentioning
confidence: 99%